Difficult temperament and negative parenting in early childhood: a genetically informed cross‐lagged analysis. Issue 2 (21st October 2015) - Micalizzi, Lauren; Wang, Manjie; Saudino, Kimberly J.
Abstract: A genetically informed longitudinal cross‐lagged model was applied to twin data to explore etiological links between difficult temperament and negative parenting in early childhood. The sample comprised 313 monozygotic (MZ) and dizygotic (DZ) twin pairs. Difficult temperament and negative parenting were assessed at ages 2 and 3 using parent ratings. Both constructs were interrelated within and across age ( r s .34–.47) and showed substantial stability ( r s .65–.68). Difficult temperament and negative parenting were influenced by genetic and environmental factors at ages 2 and 3. The genetic and nonshared environmental correlations ( r s .21–.76) at both ages suggest overlap at the level of etiology between the phenotypes. Significant bidirectional associations between difficult temperament and negative parenting were found. The cross‐lagged association from difficult temperament at age 2 to negative parenting at age 3 and from negative parenting at age 2 and difficult temperament at age 3 were due to genetic, shared environmental, and nonshared environmental factors. Substantial novel genetic and nonshared environmental influences emerged at age 3 and suggest change in the etiology of these constructs over time. Abstract : Individual differences in difficult temperament and negative parenting in early childhood are due to genetic, shared environmental, and nonshared environmental effects. In addition to contemporaneous associations at ages 2 and 3, there is evidence of a bidirectional association between difficult temperament and negative parenting across this period that is due to genetic and environmental influences.